METABOLIC RISK FACTORS OF URINARY STONE DISEASE IN CHILDREN - Tanuwidjaja, Dandy; Siregar, Safendra (Indonesian Journal of Urology, 2012)
Objective: To evaluate metabolic risk factor of urinary stone disease in children. Material & method: In this hospital-based preliminary study, children with urinary stone disease who underwent stone removal in Hasan Sadikin Hospital were included. Control group consisted children with other diseases, matched for age and BMI. Blood evaluation (uric acid, calcium and phosphate) and 24-hour urine evaluation (calcium, phosphate, sodium, magnesium, uric acid, acidity, and urine volume) were measured before the stone removal. Stone analysis was performed later. Data was analyzed using Kruskal Wallis and Spearman correlation test. Results: Eight subjects with urinary tract stone and 8 normal subjects were included to the study. This study included 4 (50%) subjects with renal stone, 3 (37,5%) subjects with bladder stone, and 1 (12,5%) subject with distal urethral stone. Stone analysis revealed 6 (75%) calcium oxalate, 1 (12,5%) calcium phosphate, and 1 (12,5%) struvite stone. There was no significant difference in blood calcium, phosphate, and uric acid between groups. 24 hours urinary calcium level was higher in subjects with stone disease (40,8 mg vs 10,6 mg, p=0,027). Urinary calcium-to-creatinine ratio was also higher in stone disease (0,23 vs 0,02 mg/mg creatinine, p=0,002). There was no significant difference of other urinary electrolites and uric acid level between groups. Conclusion: Twenty four hours urinary calcium level and urinary calcium-to-creatinine ratio is higher in children with urinary stone disease. Keywords: Urinary stone disease, children, metabolic risk factors.